Family dynamics in China and Europe in the last half-century. (April 2019) - Djundeva, Maja; Dykstra, Pearl A.; Emery, Tom
This review offers a joint perspective on Chinese and European key demographic trends in the family domain, emphasising the impact of macro-level social structures and institutions on individual life courses. We outline key demographic shifts across the Netherlands, Germany, the UK and China in the period after the 'golden age of the welfare state' in Europe and the 'post-reform' era in China (after the 1970s). Several empirical trends are highlighted, with a focus on: rising inequality in China and persistent inequality in Europe; the traditional family sequence in China and de-standardization of life courses in Europe; ending with similarities between countries in population aging and differences in later life courses with regards to intergenerational transfers. We draw upon a range of theoretical frameworks to argue that trends in marriage, fertility and intergenerational relationships reflect tensions between rapid social and economic changes and discuss the limitations of modernisation theories and the second demographic transition.